2016
DOI: 10.1051/0004-6361/201527369
|View full text |Cite
|
Sign up to set email alerts
|

Variegation of comet 67P/Churyumov-Gerasimenko in regions showing activity

Abstract: Aims. We carried out an investigation of the surface variegation of comet 67P/Churyumov-Gerasimenko, the detection of regions showing activity, the determination of active and inactive surface regions of the comet with spectral methods, and the detection of fallback material. Methods. We analyzed multispectral data generated with Optical, Spectroscopic, and Infrared Remote Imaging System (OSIRIS) narrow angle camera (NAC) observations via spectral techniques, reflectance ratios, and spectral slopes in order to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 32 publications
4
44
0
Order By: Relevance
“…The details of image registration and photometric correction steps are described in Oklay et al (2016).…”
Section: Observational Datamentioning
confidence: 99%
“…The details of image registration and photometric correction steps are described in Oklay et al (2016).…”
Section: Observational Datamentioning
confidence: 99%
“…Although the diverse interactions of their different inhomogeneities are very complex it seems that a low conductivity layer blocking further penetration of the heat wave beneath an ice rich upper layer could promote small outbursts. Here, we may have a relation to the areas with low spectral slopes and classified as active by Oklay et al (2016) which are found in our source region because the low spectral slopes may be indicative of a larger ice content at or close to the surface. It is also remarkable that the suspected source region contains a number of circular features which may be dormant gas conduits and that circular features were also suggested as sources of the outbursts of 9P/Tempel-1 by Belton (2008).…”
Section: Discussionmentioning
confidence: 88%
“…Spectral slopes are presented in Fig. 8b) showing that these regions belong to the active regions group defined by Oklay et al (2016), due to their lower spectral slopes (10−12%/100 nm between 536 nm and 882 nm) than their vicinity (12−15%/100 nm), which is in the group of mixed regions. The latter correspond to either surfaces partially covered by material ejected from active spots or inactive areas peppered with small bright spots, which are currently interpreted as minor ice deposits.…”
Section: Properties Of the Source Regionmentioning
confidence: 98%
See 2 more Smart Citations